2004
DOI: 10.1136/bmj.37952.631667.ee
|View full text |Cite
|
Sign up to set email alerts
|

Turning a blind eye: the success of blinding reported in a random sample of randomised, placebo controlled trials

Abstract: Objective To examine the reporting and success of double blinding in a sample of randomised, placebo controlled trials from leading general medicine and psychiatry journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(129 citation statements)
references
References 21 publications
4
121
1
3
Order By: Relevance
“…Lack of information on the methods used to retrieve and assess the validity of the primary studies was identified as the main deficiency. Factors associated with bias in RCTs include lack of concealment of randomization; lack of blinding of physicians, patients, outcome assessors and data analysts, and failure to report reasons for excluding patients , Juni et al 1999, Moher et al 1999b, Schulz 2000, Bhandari et al 2002a, Fergusson et al 2004. Several checklists and scales have been proposed for the assessment of study quality, which include those factors (Moher et al 1995).…”
Section: Was the Methodological Quality Of The Studies Assessed?mentioning
confidence: 99%
“…Lack of information on the methods used to retrieve and assess the validity of the primary studies was identified as the main deficiency. Factors associated with bias in RCTs include lack of concealment of randomization; lack of blinding of physicians, patients, outcome assessors and data analysts, and failure to report reasons for excluding patients , Juni et al 1999, Moher et al 1999b, Schulz 2000, Bhandari et al 2002a, Fergusson et al 2004. Several checklists and scales have been proposed for the assessment of study quality, which include those factors (Moher et al 1995).…”
Section: Was the Methodological Quality Of The Studies Assessed?mentioning
confidence: 99%
“…perfect, it was more successful than in most randomized, double-blind trials. 31,32 Measurements of urinary sucralose levels suggested a high rate of adherence. Previous trials may have yielded inconsistent results because of small samples, short duration, poor adherence, or lack of individual randomization.…”
Section: Figure 2 Urinary Sucralose Concentrationsmentioning
confidence: 99%
“…Blinding is a cornerstone of randomized clinical trials in drug evaluation (Fergusson, Glass, Waring, & Shapiro, 2004;Gaudino & Herbert, 2005;Hrobjartsson & Gotzsche, 2003. Studies of pharmacotherapies for tobacco dependence have adhered to this tradition.…”
Section: Introductionmentioning
confidence: 99%